Age-related fertility decline: is there a role for elective ovarian tissue cryopreservation?. Issue 9 (23rd June 2022) - Kasaven, Lorraine S; Saso, Srdjan; Getreu, Natalie; O'Neill, Helen; Bracewell-Milnes, Timothy; Shakir, Fevzi; Yazbek, Joseph; Thum, Meen-Yau; Nicopoullos, James; Ben Nagi, Jara; Hardiman, Paul; Diaz-Garcia, Cesar; et al.
Abstract: Age-related fertility decline (ARFD) is a prevalent concern amongst western cultures due to the increasing age of first-time motherhood. Elective oocyte and embryo cryopreservation remain the most established methods of fertility preservation, providing women the opportunity of reproductive autonomy to preserve their fertility and extend their childbearing years to prevent involuntary childlessness. Whilst ovarian cortex cryopreservation has been used to preserve reproductive potential in women for medical reasons, such as in pre- or peripubertal girls undergoing gonadotoxic chemotherapy, it has not yet been considered in the context of ARFD. As artificial reproductive technology (ART) and surgical methods of fertility preservation continue to evolve, it is a judicious time to review current evidence and consider alternative options for women wishing to delay their fertility. This article critically appraises elective oocyte cryopreservation as an option for women who use it to mitigate the risk of ARFD and introduces the prospect of elective ovarian cortex cryopreservation as an alternative.